Chinese Cultural Class - Wee-Ling, Kuan (Universiti Malaysia Sarawak (UNIMAS), 2012)
Chinese cultural component is one of the essential parts that has to be covered in the syllabus of the Mandarin proficiency course at Universiti Malaysia Sarawak. Students enjoy the cultural class very much. They have great interest in the topics covered and normally ask a lot of questions during the class. Since context matters in ensuring smoother and easier understanding of cultural knowledge by the students, sharing of stories and experience on the part of instructor has been very common when cultural class is being conducted. This article reports the most memorable experience of an instructor when “Chinese names” is taught. Students are not only learning the cultural knowledge pertaining to the language, but also the daily customs and practices as well as the ways to deal with people. This is shown when a student remembers what has been said by her instructor and applies it when communicating with her instructor.